Evidence for an Anomalous Like-Sign Dimuon Charge Asymmetry - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (Amer Physical Soc, 2010)
We measure the charge asymmetry A =(N(++) -N(--))/(N(++) + N(--)) of like-sign dimuon events in 6.1 fb(-1) of p (p) over bar collisions recorded with the D0 detector at a center-of-mass energy root s = 1: 96 TeV at the Fermilab Tevatron collider. From A we extract the like-sign dimuon charge asymmetry in semileptonic b-hadron decays: A(sl)(b) = -0.009 57 +/- 0.00251(stat) +/- 0.001 46(sys). It differs by 3.2 standard deviations from the standard model prediction A(sl)(b)(SM) = (-2.3(-0.6)(+0.5)) x 10(-4), and provides first evidence of anomalous CP violation in the mixing of neutral B mesons.